A transparent super-hydrophobic coating and preparation method thereof
By constructing a three-layer transparent superhydrophobic coating, using materials such as epoxy resin, rough structures constructed by candle soot and perfluorosilane, the problem of poor hydrophobicity of the existing coating is solved, and efficient superhydrophobicity and wear resistance are achieved.
Patent Information
- Application Number
- CN202411461723.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing superhydrophobic coatings have poor hydrophobic properties, mainly due to the imperfect micro-nano structure and insufficient content of low surface energy substances.
A transparent superhydrophobic coating with a three-layer structure is adopted, the bottom layer is epoxy resin, the middle layer is a rough structure through candle soot, and the top layer contains perfluorosilane and mesoporous silica. The hydrophobicity and wear resistance of the coating are improved through these materials and structure combinations.
The superhydrophobicity of the coating is significantly improved, the contact angle reaches above 153°, and high transparency and wear resistance are maintained, with a light transmittance of 90%.
Smart Images

Figure CN119286296B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of super hydrophobic coatings, and in particular to a transparent super hydrophobic coating and a preparation method thereof. Background Art
[0002] Superhydrophobic coatings are water-repellent and antifouling, and show resistance to stains, bacteria, proteins, and marine organisms. Existing hydrophobic coatings also have the problem of imperfect surface micro-nanostructures: The hydrophobicity of superhydrophobic coatings mainly depends on special micro-nanostructures that enable water droplets to form a high contact angle on the surface. If the structure is imperfect, such as insufficient or uneven roughness, the contact area between the water droplet and the surface will increase, thereby reducing the hydrophobicity. For example, during the preparation process, improper control of process parameters may cause the micro-nanostructure to be incomplete or inconsistent in size.
[0003] At the same time, the chemical composition of the coating plays a key role in hydrophobicity. If there is a lack of low surface energy substances, or their content is insufficient or unevenly distributed, it is difficult to form a stable super-hydrophobic surface. For example, although some coatings contain low surface energy substances, they may have poor hydrophobicity due to low content or loose combination with other components.
[0004] Therefore, how to prepare a coating with excellent superhydrophobic properties has important research value and significance. Summary of the invention
[0005] The present invention provides a transparent super-hydrophobic coating and a preparation method thereof, which solves the problem of poor hydrophobicity of the coating in the related art.
[0006] The technical solution of the present invention is as follows:
[0007] The present invention provides a transparent super-hydrophobic coating, which comprises a bottom layer, a middle layer, and a top layer from bottom to top;
[0008] The raw materials of the bottom layer include epoxy resin, curing agent and solvent in a mass ratio of 1:0.5:50-60;
[0009] The middle layer is a rough structure layer constructed using candle ash;
[0010] The raw materials of the top layer include fluorine-containing silane and solvent in a ratio of 1:200-300.
[0011] As a further technical solution, the fluorine-containing silane includes one or both of perfluorooctyltriethoxysilane and heptadecafluorooctyltriethoxysilane.
[0012] As a further technical solution, the fluorine-containing silane is perfluorooctyltriethoxysilane and heptadecafluorooctyltriethoxysilane in a mass ratio of 5:3 to 4:1.
[0013] In the present invention, by using perfluorooctyltriethoxysilane and heptadecafluorooctyltriethoxysilane in a mass ratio of 5:3 to 4:1, the wear resistance of the coating is further improved while ensuring the hydrophobicity of the coating.
[0014] As a further technical solution, the raw material of the top layer also includes mesoporous silica, and the mass volume ratio of the mesoporous silica to the fluorine-containing silane is 0.3~0.8g:1mL.
[0015] In the present invention, mesoporous silica is also added to the top raw material of the super hydrophobic coating, which further improves the wear resistance of the coating.
[0016] As a further technical solution, the mesoporous silica is titanium carbide modified mesoporous silica.
[0017] As a further technical solution, the preparation method of titanium carbide modified mesoporous silica comprises the following steps: mixing titanium carbide, mesoporous silica and polyvinyl alcohol solution, and calcining to obtain titanium carbide modified mesoporous silica;
[0018] The polyvinyl alcohol solution is composed of polyvinyl alcohol and a solvent in a mass volume ratio of 1g:50-60mL;
[0019] The mass ratio of the titanium carbide, mesoporous silica and polyvinyl alcohol is 1:5-8:0.5.
[0020] In the present invention, the mesoporous silicon dioxide is modified by using titanium carbide to further improve the wear resistance of the coating.
[0021] The present invention also proposes a method for preparing a transparent super-hydrophobic coating, comprising the following steps:
[0022] S1, bottom layer: mixing epoxy resin, curing agent and solvent by ultrasonic mixing to obtain a bottom layer solution; coating the bottom layer solution on the substrate and letting it stand to obtain a semi-cured EP bottom layer coating;
[0023] S2, middle layer: placing the semi-cured bottom layer coating above the center of the candle flame, covering the soot, obtaining the EP@CS coating, cooling, annealing, cooling, and obtaining the EP@CS (O) coating;
[0024] S3, top layer: after stirring and mixing the fluorine-containing silane and the solvent, a fluorine-containing silane modified solution is obtained, the EP@CS(O) coating is immersed in the fluorine-containing silane modified solution, taken out and cured, and the EP@F-CS(O) super-hydrophobic coating is obtained.
[0025] As a further technical solution, the introduction time of the soot is 60 to 300 seconds.
[0026] As a further technical solution, the substrate is a glass slide; the substrate has also been pre-treated by cleaning;
[0027] As a further technical solution, in step S1, the ultrasonication time is 1 to 2 hours; and the standing time is 20 to 25 minutes.
[0028] As a further technical solution, in step S2, the annealing is performed at a heating rate of 10-15°C / min to a temperature of 440-450°C for 40-50 minutes.
[0029] As a further technical solution, in step S3, the stirring and mixing time is 30-40 minutes; the soaking time is 4-5 hours; the curing temperature is 80-85°C, and the curing time is 2-2.5 hours.
[0030] The working principle and beneficial effects of the present invention are:
[0031] In the present invention, a super-hydrophobic coating is constructed with a bottom layer of an epoxy resin layer, a middle layer of a rough structure layer constructed using candle ash, and a top layer of a fluorine-containing silane layer. The contact angle of the super-hydrophobic coating can reach more than 153°, which significantly improves the super-hydrophobicity of the coating. The light transmittance of the coating is almost the same as that of bare glass, reaching 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0033] Figure 1 This is a contact angle test diagram of the super-hydrophobic coating prepared in Example 1 of the present invention;
[0034] Figure 2 The SEM images of the super-hydrophobic coatings prepared in Example 1 and Comparative Examples 2-3 of the present invention are shown in FIG.
[0035] In the figure, (a) and (d) are EP@CS coatings prepared in Comparative Example 2, (b) and (e) are EP@CS(O) coatings prepared in Comparative Example 3, and (c) and (f) are EP@F-CS(O) coatings prepared in Example 1;
[0036] Figure 3 This is a light transmittance test diagram of the super hydrophobic coating of the present invention.
[0037] In the figure, CS-1 represents the super-hydrophobic coating obtained by introducing soot for 60 seconds in Example 1, CS-2 represents the super-hydrophobic coating obtained by introducing soot for 120 seconds, CS-3 represents the super-hydrophobic coating obtained by introducing soot for 180 seconds, CS-4 represents the super-hydrophobic coating obtained by introducing soot for 240 seconds, CS-5 represents the super-hydrophobic coating obtained by introducing soot for 300 seconds, and Control represents bare glass;
[0038] Figure 4 This is a self-cleaning experiment diagram of the super-hydrophobic coating prepared in Example 1 of the present invention;
[0039] Figure 5 This is a frame diagram of a water drop adhesion experiment on the surface of a super-hydrophobic coating prepared in Example 1 of the present invention;
[0040] Figure 6 This is a frame diagram of the bouncing property of water droplets on the surface of the super-hydrophobic coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] A method for preparing a transparent super-hydrophobic coating comprises the following steps:
[0044] S1. Slide Pretreatment
[0045] The slide was ultrasonically cleaned with ethanol and deionized water for 30 min in sequence, and then left to dry at room temperature for later use;
[0046] S2, bottom layer
[0047] Epoxy resin (EP), curing agent and ethanol in a volume ratio of 1:0.5:50 were mixed in a 100 mL beaker, and ultrasonicated for 1 h at room temperature to obtain a base solution with good adhesion; the prepared EP base solution was coated on a pretreated glass slide with a 60 μm coating rod, and allowed to stand at room temperature for 20 min to obtain a semi-cured EP base coating;
[0048] S3, middle layer
[0049] Use candle soot to construct a rough structure. Place the EP coating sample 1 cm above the center of the candle flame and move it back and forth horizontally for 60 seconds until the glass slide is completely covered with soot (CS), presenting a dense and uniform carbon black surface, and obtain the EP@CS coating; after it cools to room temperature, place the templated coating sample in a muffle furnace at 440°C for annealing for 40 minutes (heating rate of 10°C / min); finally, after the temperature naturally cools to below 100°C, take out the sample to obtain the EP@CS (O) coating;
[0050] S4, top layer
[0051] 0.3 mL of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane was added to 60 mL of ethanol solution respectively, and magnetic stirring was performed at room temperature for 30 min to obtain 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane modified solution; the EP@CS (O) coating was immersed in the modified solution for 4 h, then taken out and placed in an oven for curing at 80 ° C for 2 h to obtain the final EP@F-CS (O) superhydrophobic coating.
[0052] Example 2
[0053] A method for preparing a transparent super-hydrophobic coating comprises the following steps:
[0054] S1. Slide Pretreatment
[0055] The slide was ultrasonically cleaned with ethanol and deionized water for 40 min in sequence, and then left to dry at room temperature for later use;
[0056] S2, bottom layer
[0057] Epoxy resin (EP), curing agent and ethanol in a volume ratio of 1:0.5:55 were mixed in a 100 mL beaker, and ultrasonicated for 1.5 h at room temperature to obtain a base solution with good adhesion; the prepared EP base solution was coated on a pretreated glass slide with a 60 μm coating rod, and allowed to stand at room temperature for 20 min to obtain a semi-cured EP base coating;
[0058] S3, middle layer
[0059] Use candle soot to construct a rough structure. Place the EP coating sample 1 cm above the center of the candle flame and move it back and forth horizontally for 60 seconds until the glass slide is completely covered with soot (CS), presenting a dense and uniform carbon black surface, and obtain the EP@CS coating; after it cools to room temperature, place the templated coating sample in a muffle furnace at 450°C for annealing for 45 minutes (heating rate of 12°C / min); finally, after the temperature naturally cools to below 100°C, take out the sample to obtain the EP@CS (O) coating;
[0060] S4, top layer
[0061] 0.3 mL of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane was added to 60 mL of ethanol solution respectively, and magnetic stirring was performed at room temperature for 30 min to obtain 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane modified solution; the EP@CS (O) coating was immersed in the modified solution for 4 h, then taken out and placed in an oven for curing at 85 ° C for 2 h to obtain the final EP@F-CS (O) superhydrophobic coating.
[0062] Example 3
[0063] A method for preparing a transparent super-hydrophobic coating comprises the following steps:
[0064] S1. Slide Pretreatment
[0065] The slide was ultrasonically cleaned with ethanol and deionized water for 30 min in sequence, and then left to dry at room temperature for later use;
[0066] S2, bottom layer
[0067] Epoxy resin (EP), curing agent and ethanol in a volume ratio of 1:0.5:60 were mixed in a 100 mL beaker, and ultrasonicated for 2 h at room temperature to obtain a base solution with good adhesion; the prepared EP base solution was coated on a pretreated glass slide with a 60 μm coating rod, and allowed to stand at room temperature for 25 min to obtain a semi-cured EP base coating;
[0068] S3, middle layer
[0069] Use candle soot to construct a rough structure. Place the EP coating sample 1 cm above the center of the candle flame and move it back and forth horizontally for 60 seconds until the glass slide is completely covered with soot (CS), presenting a dense and uniform carbon black surface, and obtain the EP@CS coating; after it cools to room temperature, place the templated coating sample in a muffle furnace at 440°C for annealing for 50 minutes (heating rate of 10°C / min); finally, after the temperature naturally cools to below 100°C, take out the sample to obtain the EP@CS (O) coating;
[0070] S4, top layer
[0071] 0.3 mL of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane was added to 60 mL of ethanol solution respectively, and magnetic stirring was performed at room temperature for 30 min to obtain 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane modified solution; the EP@CS (O) coating was immersed in the modified solution for 5 h, then taken out and placed in an oven for curing at 80 ° C for 2.5 h to obtain the final EP@F-CS (O) superhydrophobic coating.
[0072] Example 4
[0073] The only difference between this embodiment and embodiment 1 is that 1H,1H,2H,2H-perfluorooctyltriethoxysilane is replaced by heptadecafluorooctyltriethoxysilane.
[0074] Example 5
[0075] The difference between this embodiment and embodiment 1 is that half the mass of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is replaced with an equal amount of heptadecafluorooctyltriethoxysilane.
[0076] Example 6
[0077] The difference between this embodiment and embodiment 1 is that one sixth of the mass of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is replaced with heptadecafluorooctyltriethoxysilane.
[0078] Example 7
[0079] The difference between this embodiment and embodiment 1 is that one fifth of the mass of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is replaced with heptadecafluorooctyltriethoxysilane.
[0080] Example 8
[0081] The only difference between this embodiment and embodiment 1 is that three eighths of the mass of 1H,1H,2H,2H-perfluorooctyltriethoxysilane is replaced with heptadecafluorooctyltriethoxysilane.
[0082] Example 9
[0083] The only difference between this embodiment and embodiment 8 is that mesoporous silica is added to the ethanol solution during stirring in step S4.
[0084] Example 10
[0085] The only difference between this embodiment and embodiment 8 is that during the stirring in step S4, titanium carbide-modified mesoporous silica is also added to the ethanol solution;
[0086] The preparation method of titanium carbide modified mesoporous silica comprises the following steps: titanium carbide, mesoporous silica and polyvinyl alcohol solution are mixed and calcined to obtain titanium carbide modified mesoporous silica; wherein the polyvinyl alcohol solution is composed of polyvinyl alcohol and water in a mass volume ratio of 1 g:50 mL; and the mass ratio of titanium carbide, mesoporous silica and polyvinyl alcohol is 1:5:0.5.
[0087] Embodiment 11
[0088] The only difference between this embodiment and embodiment 8 is that during stirring in step S4, titanium carbide-modified mesoporous silica is also added to the ethanol solution; the preparation method of titanium carbide-modified mesoporous silica comprises the following steps: titanium carbide, mesoporous silica, and polyvinyl alcohol solution are mixed and calcined to obtain titanium carbide-modified mesoporous silica; wherein the polyvinyl alcohol solution is composed of polyvinyl alcohol and water in a mass volume ratio of 1g:80mL; the mass ratio of titanium carbide, mesoporous silica, and polyvinyl alcohol is 1:8:0.5.
[0089] Comparative Example 1
[0090] A method for preparing a transparent super-hydrophobic coating comprises the following steps:
[0091] S1. Slide Pretreatment
[0092] The slide was ultrasonically cleaned with ethanol and deionized water for 30 min in sequence, and then left to dry at room temperature for later use;
[0093] S2, bottom layer
[0094] Epoxy resin (EP), curing agent and ethanol in a volume ratio of 1:0.5:50 were mixed in a 100 mL beaker and ultrasonicated at room temperature for 1 hour to obtain a base solution with good adhesion; the prepared EP base solution was coated on a pretreated glass slide with a 60 μm coating rod and allowed to stand at room temperature for 20 minutes to obtain an EP coating.
[0095] Comparative Example 2
[0096] A method for preparing a transparent super-hydrophobic coating comprises the following steps:
[0097] S1. Slide Pretreatment
[0098] The slide was ultrasonically cleaned with ethanol and deionized water for 30 min in sequence, and then left to dry at room temperature for later use;
[0099] S2, bottom layer
[0100] Epoxy resin (EP), curing agent and ethanol in a volume ratio of 1:0.5:50 were mixed in a 100 mL beaker, and ultrasonicated for 1 h at room temperature to obtain a base solution with good adhesion; the prepared EP base solution was coated on a pretreated glass slide with a 60 μm coating rod, and allowed to stand at room temperature for 20 min to obtain a semi-cured EP base coating;
[0101] S3, middle layer
[0102] The rough structure was constructed using candle soot. The EP coating sample was placed 1 cm above the center of the candle flame and moved horizontally back and forth for 60 seconds until the slide was completely covered with soot (CS), presenting a dense and uniform carbon black surface, and the EP@CS coating was obtained.
[0103] Comparative Example 3
[0104] A method for preparing a transparent super-hydrophobic coating comprises the following steps:
[0105] S1. Slide Pretreatment
[0106] The slide was ultrasonically cleaned with ethanol and deionized water for 30 min in sequence, and then left to dry at room temperature for later use;
[0107] S2, bottom layer
[0108] Epoxy resin (EP), curing agent and ethanol in a volume ratio of 1:0.5:50 were mixed in a 100 mL beaker, and ultrasonicated for 1 h at room temperature to obtain a base solution with good adhesion; the prepared EP base solution was coated on a pretreated glass slide with a 60 μm coating rod, and allowed to stand at room temperature for 20 min to obtain a semi-cured EP base coating;
[0109] S3, middle layer
[0110] Use candle soot to construct a rough structure. The EP coating sample was placed 1 cm above the center of the candle flame and moved horizontally back and forth for 60 seconds until the glass slide was completely covered with soot (CS), presenting a dense and uniform carbon black surface, and the EP@CS coating was obtained; after it cooled to room temperature, the templated coating sample was placed in a muffle furnace at 440°C for annealing for 40 minutes (heating rate of 10°C / min); finally, after the temperature naturally cooled to below 100°C, the sample was taken out to obtain the EP@CS (O) coating.
[0111] like Figure 1 As shown, the contact angle of the super-hydrophobic coating prepared in Test Example 1 is 153±1°C.
[0112] like Figure 2 The SEM images of the super-hydrophobic coatings prepared in Example 1 and Comparative Examples 1 to 3 show that the coating surface of Example 1 has greater roughness and stronger hydrophobicity.
[0113] like Figure 3 As shown, the introduction time of soot was changed: in step S3 of Example 1, the soot was introduced 1 cm above the center of the candle flame and moved horizontally back and forth for 60 seconds, that is, the time for introducing soot was 60 seconds, and the coating prepared in Example 1 was recorded as CS-1;
[0114] On the basis of Example 1, only the time of introducing soot was changed, and the time of introducing soot was 120s, 180s, 240s, and 300s, respectively. The coatings finally obtained were recorded as CS-2, CS-3, CS-4, and CS-5, respectively. The transmittance of bare glass (referred to as Control), CS-1, CS-2, CS-3, CS-4, and CS-5 was tested respectively. It can be found that the transmittance of the obtained superhydrophobic coating is almost the same as that of the bare glass, about 90%, and has excellent transparency.
[0115] The contact angles of the super-hydrophobic coatings prepared in Examples 2 to 11 were all above 153±1°C;
[0116] The wear resistance test of the super-hydrophobic coatings prepared in Example 1 and Examples 4 to 11 was performed respectively:
[0117] Wear resistance: Place the sample on 320-mesh SiC sandpaper with the coating facing downward and in contact with the sandpaper. Then place a 200g weight on a glass sheet. Then use tweezers to push the glass sheet forward 10cm in a straight line. Then rotate the pushing direction 90° clockwise and push it forward 10cm in a straight line. This is recorded as one wear cycle. The wear distance of each cycle is 20cm. The distance at which the coating loses its superhydrophobicity is recorded.
[0118] The wear resistance test results are shown in Table 1 below.
[0119] Table 1 Wear resistance test results of super hydrophobic coating
[0120]
[0121] Compared with Example 1 and Examples 4 to 6, the super hydrophobic coatings prepared in Examples 7 to 8 have a longer wear resistance distance, indicating that by using perfluorooctyltriethoxysilane and heptadecafluorooctyltriethoxysilane in a mass ratio of 5:3 to 4:1, the hydrophobicity of the coating is ensured while further improving the wear resistance of the coating.
[0122] Compared with Example 8, the super hydrophobic coating prepared in Example 9 has a longer wear resistance distance, indicating that mesoporous silica is also added to the top raw material of the super hydrophobic coating, which further improves the wear resistance of the coating.
[0123] Compared with Example 9, the super hydrophobic coatings prepared in Examples 10 to 11 have a longer wear resistance distance, indicating that the wear resistance of the coating is further improved by modifying the mesoporous silica with titanium carbide.
[0124] Self-cleaning experiment
[0125] Figure 4Figures a to d are self-cleaning performance test graphs of the original glass (left) and the super-hydrophobic EP@F-CS(O) coating prepared in Example 1 (right). Methyl orange dye (orange powder) is used as a model pollutant. It can be seen that the super-hydrophobic EP@F-CS(O) coating prepared in this application has excellent self-cleaning performance.
[0126] Water drop adhesion test
[0127] When the water droplet is ≤6 μL, the water droplet is non-adhesive on the surface of the coating prepared in Example 1 and cannot stay on the surface of the coating. The specific frame diagram of the water droplet adhesion is as follows: Figure 5 shown.
[0128] Water drop bouncing experiment
[0129] When the volume of the water droplet reaches 7 μL, the water droplet automatically falls to the surface of the coating prepared in Example 1 under the action of neutrality. The specific frame diagram of the water droplet bouncing is as follows: Figure 6 As shown in the figure, it can be seen that even without any external force or tilt angle, water droplets will automatically bounce off the coating surface.
[0130] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A transparent super-hydrophobic coating, characterized in that: From bottom to top, it includes the bottom layer, middle layer, and top layer; The raw materials of the bottom layer include epoxy resin, curing agent and solvent in a mass ratio of 1:0.5:50-60; The middle layer is a rough structure layer constructed using candle ash; The raw materials of the top layer include fluorine-containing silane and solvent in a ratio of 1:200-300; The method for preparing the transparent super-hydrophobic coating comprises the following steps: S1, bottom layer: mixing epoxy resin, curing agent and solvent by ultrasonic mixing to obtain a bottom layer solution; coating the bottom layer solution on the substrate and letting it stand to obtain a semi-cured EP bottom layer coating; S2, middle layer: placing the semi-cured bottom layer coating above the center of the candle flame, covering the soot, obtaining the EP@CS coating, cooling, annealing, cooling, and obtaining the EP@CS (O) coating; S3, top layer: after stirring and mixing the fluorine-containing silane and the solvent, a fluorine-containing silane modified solution is obtained, the EP@CS(O) coating is immersed in the fluorine-containing silane modified solution, taken out and cured, and the EP@F-CS(O) super-hydrophobic coating is obtained.
2. A transparent super-hydrophobic coating according to claim 1, characterized in that: The fluorine-containing silane includes one or both of perfluorooctyltriethoxysilane and heptadecafluorooctyltriethoxysilane.
3. A transparent super-hydrophobic coating according to claim 2, characterized in that: The fluorine-containing silane is perfluorooctyltriethoxysilane and heptadecafluorooctyltriethoxysilane in a mass ratio of 5:3 to 4:
1.
4. A transparent super-hydrophobic coating according to claim 1, characterized in that: The raw material of the top layer also includes mesoporous silica, and the mass volume ratio of the mesoporous silica to the fluorine-containing silane is 0.3-0.8 g:1 mL.
5. A transparent super-hydrophobic coating according to claim 4, characterized in that: The mesoporous silica is titanium carbide modified mesoporous silica.
6. A transparent super-hydrophobic coating according to claim 5, characterized in that: The preparation method of titanium carbide modified mesoporous silica comprises the following steps: mixing titanium carbide, mesoporous silica and polyvinyl alcohol solution, and calcining to obtain titanium carbide modified mesoporous silica; The polyvinyl alcohol solution is composed of polyvinyl alcohol and a solvent in a mass volume ratio of 1g:50-60mL; The mass ratio of the titanium carbide, mesoporous silica and polyvinyl alcohol is 1:5-8:0.
5.
7. A transparent super-hydrophobic coating according to claim 1, characterized in that: In step S1, the ultrasonication time is 1-2 hours; and the standing time is 20-25 minutes.
8. A transparent super-hydrophobic coating according to claim 1, characterized in that: In step S2, during the annealing, the temperature is raised to 440-450° C. at a heating rate of 10-15° C. / min for 40-50 min.
9. A transparent super-hydrophobic coating according to claim 1, characterized in that: In step S3, the stirring and mixing time is 30-40 minutes; the soaking time is 4-5 hours; the curing temperature is 80-85° C., and the curing time is 2-2.5 hours.
Citation Information
Patent Citations
Super-hydrophobic coating containing candle soot and preparation method of same
CN105523722A
Super-hydrophobic coating as well as preparation method and application thereof
CN114833054A